RESTORATIVE JUSTICE IMPLEMENTATION AGAINST THE PERPETRATOR OF EMBEZZLEMENT IN OFFICE AT PT KARYA NIAGA ABADI - Sinjaya, Andi; Marjani, Ani (jfpublisher, 2022)
The development of the times requires humans to adopt certain lifestyles that are considered as urgent needs. However, along with this development, there is an increase in deviant behavior that is against the rules, thus triggering various criminal acts in the society. One of the consequences of the evolving consumptive lifestyle is the increasing role of expedition companies as providers of goods delivery services. However, in its operations, the expedition company cannot completely avoid criminal acts, including embezzlement in office committed by employees. This research aims to identify the factors that cause embezzlement in office and analyze the settlement process in the expedition company. This research uses empirical legal research methods to examine positive legal provisions in relation to the reality that occurs in society. The approach used in this research is empirical juridical approach. The findings indicate that the criminal case settlement of embezzlement in office at PT Karya Niaga Abadi prioritizes the restorative justice method. In the settlement process, the victim, perpetrator, and related parties are involved to seek the best solution to the case. In addition, the approach of restorative justice also aims to provide compensation to victims for criminal acts committed by the perpetrators.